Evaluating feedstocks for carbon dioxide removal by enhanced rock weathering and CO2 mineralization - Paulo, Carlos; Power, Ian M.; Stubbs, Amanda R.; Wang, Baolin; Zeyen, Nina; Wilson, Sasha (Applied geochemistry, 2021)
Mineralogically complex feedstocks, including kimberlite, serpentinite, and wollastonite skarns, have vast capacities to sequester carbon dioxide (CO2) through enhanced rock weathering and CO2 mineralization. However, only a small reactive fraction of these feedstocks will be accessible for carbon dioxide removal at Earth's surface conditions. We have developed a new method to evaluate the reactivity of mineral feedstocks that consists of a batch leach test using CO2 coupled with total inorganic carbon (TIC) analysis to quantify easily extractable Mg and Ca from non-carbonate (desirable) cation sources. Kimberlite residues from the Venetia Diamond Mine (South Africa), serpentinites, wollastonite skarn, and brucite ore were tested and the results were compared to those from commercial ammonium acetate (NH4OAc) leach tests. A strong correlation (R2 = 0.99) between leached Ca and TIC showed that carbonate minerals (e.g., calcite in kimberlite) are a substantial and undesirable source of easily extractable cations that must be excluded in calculating CO2 sequestration potential. Silicate dissolution (e.g., serpentine) was inferred from the strong positive correlation (R2 = 0.94) between Mg and Si concentrations leached from kimberlites and serpentinites. Strong correlations between leached Ca and Si were only detected for wollastonite skarns, whereas Mg leaching from samples with high abundances of brucite showed weak or no relationship to TIC or Si. The ability to distinguish between sources (non-carbonate versus carbonate) of easily extractable cations is necessary to accurately assess CO2 sequestration potential. The maximum CO2 storage capacity of the Venetia kimberlites was 268–342 kg CO2/t, and our leach test estimated an accessible potential in the range of 3–9 kg CO2/t when only accounting for non-carbonate sources. Our CO2 batch leach test is useful to evaluate the reactivity of mineralogically complex feedstocks at Earth's surface conditions for the purpose of carbon dioxide removal. •CO2 mineralization at Earth's surface conditions is limited by cation release from mineral feedstocks.•CO2 batch leaching coupled with carbon analysis provides an accurate assessment of feedstock reactivity.•Cation and TIC correlation allows for distinction between non-carbonate and carbonate sources.•Contributions of extractable cations from carbonates leads to overestimation of CO2 sequestration potential.•An offset of 7–20% of the CO2 emissions from the Venetia Diamond Mine is achievable at Earth's surface conditions.